Bipolar disorder and eating disorders in sport: a case of comorbidity and review of treatment principles in an elite athlete - Bradley, S. L.; Reardon, C. L. (The Physician and Sportsmedicine, 2022)
Objectives There is overlap between the typical age of onset of bipolar disorder (BD) and the age of peak athletic success. Additionally, eating disorders (EDs) are prevalent psychiatric disorders in athletes. Despite the relevance of both disorders in this population, there remains a need for treatment guidelines, especially when present as comorbidities given the complex interplay between them.